2011
DOI: 10.1242/jeb.051714
|View full text |Cite
|
Sign up to set email alerts
|

A hydrodynamic sensory antenna used by killifish for nocturnal hunting

Abstract: SUMMARYThe perception of sensory stimuli by an animal requires several steps, commencing with the capture of stimulus energy by an antenna that, as the interface between the physical world and the nervous system, modifies the stimulus in ways that enhance the animal's perception. The mammalian external ear, for example, collects sound and spectrally alters it to increase sensitivity and improve the detection of directionality. In view of the morphological diversity of the lateral-line system across species and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…We speculate that an advantage of such fast locomotion is to avoid underwater predators like fish, which have been known to detect capillary waves on the surface of a pond generated by trapped insects that fall on the fluid surface (Schwarz et al, 2011). We have shown that manoeuvres in the transition between different flight modesinterfacial, airborne and backward -are controlled by postural changes.…”
Section: Discussionmentioning
confidence: 92%
“…We speculate that an advantage of such fast locomotion is to avoid underwater predators like fish, which have been known to detect capillary waves on the surface of a pond generated by trapped insects that fall on the fluid surface (Schwarz et al, 2011). We have shown that manoeuvres in the transition between different flight modesinterfacial, airborne and backward -are controlled by postural changes.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the mottled sculpin, Cottus bairdi, demonstrates an orienting response to free-swimming prey (Hoekstra and Janssen, 1985), and responds to a dipole stimulus generated by a vibrating sphere . The striped panchax (Aplocheilus lineatus, a killifish) detects and reorients towards the source of surface waves generated by an oscillating probe (Bleckmann et al, 1981) or a small, falling pellet (1 mm diameter; Schwarz et al, 2011). Similarly, blind cavefish (Astyanax mexicanus) swim toward surface disturbances generated by falling clay particles in cave pools or by a vibrating rod in the laboratory, while the sighted surface-dwelling form of this species rarely exhibits these behaviors in darkness (Yoshizawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the presence of morphological and physiological specializations of individual sensory systems (e.g. Livingston, 1987;Schwarz et al, 2011) is traditionally used as an indication of the enhancement of behavioral capabilities. This correlation provides evidence for adaptive evolution, but the link between sensory morphology and prey detection behavior is not always clear.…”
Section: Introductionmentioning
confidence: 99%